Configurational entropy of a set of dipoles placed on a two-dimensional lattice - Dammig Quiña, Pablo Leandro (2017)
In the present work we calculate the configurational entropy of an arbitrary number of dipoles placed on a square lattice. We use a quasi-two-dimensional (Q2D) space to capture the main features determining the occupation statistics of this system. We show that our result is in agreement with both, lattice-gas predictions at low coverages and the exact value derived in the close-packed limit as well. Therefore our equation provides a substantial improvement to the most recent calculations based on semiempirical models and Monte Carlo simulations.